International Journal of Chemical Reactor Engineering (De Gruyter, 2003)
The International Journal of Chemical Reactor Engineering covers the broad fields of theoretical and applied reactor engineering. The IJCRE covers topics drawn from the substantial areas of overlap between catalysis, reaction and reactor engineering. Authors include notable international professors and R&D industry leaders.